FOREVER YOUNG FLOWER Negatively Regulates Ethylene Response DNA-Binding Factors by Activating an Ethylene-Responsive Factor to Control Arabidopsis Floral Organ Senescence and Abscission - Chen, Wei-Han (Plant Physiol, 2015)
In this study of Arabidopsis (Arabidopsis thaliana), we investigated the relationship between FOREVER YOUNG FLOWER (FYF) and Ethylene Response DNA-binding Factors (EDFs) and functionally analyzed a key FYF target, an Ethylene-Responsive Factor (ERF), that controls flower senescence/abscission. Ectopic expression of EDF1/2/3/4 caused promotion of flower senescence/abscission and the activation of the senescence-associated genes. The presence of a repressor domain in EDFs and the enhancement of the promotion of senescence/abscission in EDF1/2/3/4+SRDX (converting EDFs to strong repressors by fusion with the ERF-associated amphiphilic repression motif repression domain SRDX) transgenic plants suggested that EDFs act as repressors. The significant reduction of β-glucuronidase (GUS) expression by 35S:FYF in EDF1/2/3/4:GUS plants indicates that EDF1/2/3/4 functions downstream of FYF in regulating flower senescence/abscission. In this study, we also characterized an ERF gene, FOREVER YOUNG FLOWER UP-REGULATING FACTOR1 (FUF1), which is up-regulated by FYF during flower development. Ectopic expression of FUF1 caused similar delayed flower senescence/abscission as seen in 35S:FYF plants. This phenotype was correlated with deficient abscission zone formation, ethylene insensitivity, and down-regulation of EDF1/2/3/4 and abscission-associated genes in 35S:FUF1 flowers. In contrast, significant promotion of flower senescence/abscission and up-regulation of EDF1/2/3/4 were observed in 35S:FUF1+SRDX transgenic dominant-negative plants, in which FUF1 is converted to a potent repressor by fusion to an SRDX-suppressing motif. Thus, FUF1 acts as an activator in suppressing EDF1/2/3/4 function and senescence/abscission of the flowers. Our results reveal that FYF regulates flower senescence/abscission by negatively regulating EDF1/2/3/4, which is the downstream gene in the ethylene response, by activating FUF1 in Arabidopsis.